Optimal Design of the Linkage Mechanism Simulation of Three-Roller Guiding Device - Zhang Yiwei; Yang Wei; Tang Ligang (Jixie chuandong)
In order to improve the method to design the linkage mechanism of three-roller guiding device installed at the exit of piercing mill,the mathematical model of the multi objective optimal design is established based on comprehensive consideration of the technical requirement,the operation condition and the transmission performance of the mechanism.The fully parameterized virtual prototyping model of mechanism is optimized by simulation to determine the design parameter in the ADAMS environment.Under the given constraints,the simulation results show that the comprehensive performance of the mechanism is significantly improved.